MEKANISME KEBIJAKAN ZONA INTEGRITAS ATAS UPAYA REFORMASI BIROKRASI DI PENGADILAN NEGERI MAKASSAR PRESPEKTIF SIYASAH SYAR’IYYAH - suci, Nandita Fahira; Kurniati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
The aim of this research is to describe the implementation of the integrity zone in the bureaucracy at the Makassar District Court from a siyasah syar’iyyah perspective, obstacles in implementing the integrity zone from a siyasah syar’iyyah perspective, efforts to implement the integrity zone policy at the Makassar District Court from a siyasah syar’iyyah perspective. The results of this research are that it was carried out well by planning to create a sterile regional program that can only be accessed by administrative judges through one-stop integrated services, by supervising and providing quality facilities and of course good service, based on the results of interviews and The researcher’s observation is that there is none, because the integrity zone is a commitment that must be implemented in order to realize WBK and WBBM. However, from the perspective of siyasah syar’iyyah, if it is related to the complexity of the problems studied, it conveys its view that especially as a legitimate institution of Islam, its main premise is openness or religion, especially supernatural qualities and standards from Allah which are accepted as truth and justice, so it is also accepted that this is the source of optimal regulation.